Childhood maltreatment compromises resilience against occupational trauma exposure: A retrospective study among emergency medical service personnel. (January 2020) - Behnke, Alexander; Rojas, Roberto; Karabatsiakis, Alexander; Kolassa, Iris-Tatjana
Abstract: Background: Childhood maltreatment (CM) compromises resilience against stress and trauma throughout life. Therefore, it could present a major risk factor for the health of frequently trauma-exposed professionals such as emergency medical service (EMS) personnel. Objective: We investigated, whether EMS personnel's history of CM increased their risk for mental and physical stress symptoms after occupational trauma exposure. Participants and Setting: Data from 103 German EMS personnel (age: Mdn ± QD = 26.00 ± 8.50 years) were collected as part of a cross-sectional survey distributed among employees of the regional German Red Cross EMS division (response rate 46.6%). The sample corresponded well to the division's entire staff in terms of socio-anagraphic characteristics. Methods: CM and occupational trauma exposure as well as posttraumatic, depressive, and somatic symptoms were assessed with self-report questionnaires. Results: Moderation analyses indicated stronger positive associations between occupational trauma exposure and the severity of posttraumatic (β = .30, p < .001), depressive (β = .20, p = .026), and somatic symptoms (β = .18, p = .059) among EMS personnel who reported a higher exposure to CM. Conclusions: Our study provides initial evidence that CM could increase the EMS personnel's vulnerability to the detrimental consequences of critical incidents on duty. Future research is needed (i) to replicate and generalize our observation on various trauma-exposed professions as well as (ii) to develop preventive measures for targeting the mediating and protective factors which influence the relationship between CM and the negative consequences of occupational trauma exposure.